Uma proposta de ensino e aprendizagem de Língua Inglesa integrada ao uso das TICS para o desenvolvimento da autonomia dos aprendizes - Silva, Francisco Alan da (2011)
This study focuses on the teaching and learning of English based on a new theoretical perspective concerning the Zone of Proximal Development (ZPD), which points to the apprehension of metacognitive processes as the way to reach learning autonomy. The theoretical set underline this study is those of a new pedagogy based on the symbiosis of Bruner‟s (2002) and Freire‟s (2009) concepts and in the metacognitive theory. In a social context dominated by the Communication and Information Technologies (CIT), the integration between teacher and learners with the support of the internet has been used as the way to operationalize this new emergent proposal of the theoretical perspectives. The analyses have been conducted through Systemic and Integral Action Research. The results at the end of this study corroborate our hypothesis that the enlargement of spontaneous knowledge of the learners can facilitate the understanding of scientific concepts, stimulating their metacognition and thus promoting their autonomy.